Caracterización fenotípica de la cabra criolla y su sistema de producción, en la parroquia Mangahurco del cantón Zapotillo - Camacho Enriquez, Osvaldo Vladimiro (2018)
The present work was carried out in the Mangahurco parish, cantón Zapotillo, which is located at a distance of 280 km from the provincial capital (Loja) and 63 km from the cantonal capital of Zapotillo. The objective was to phenotypically identify the Creole goat and its production system in which it is being exploited and to determine the productive, reproductive and zoometric parameters. 17 goat herds participated, with a number of 93 animals under study, during the investigation two visits were made with an interval of 64 days. For the phenotypic identification, 18 zoomometric and 8 phaneroptic measurements were taken, and to establish its production system, productive and reproductive parameters, the information was obtained through a survey. From the results obtained, it can be determined that the racial biotype of this Creole goat is long and short, straight and short, straight profile, with horns, only 10% of the population has mamelas, with a coat attached to the body where two colors of black and brown main mantles predominate, and with irregular spots along the length and width of its body, it presents a globose udder and most of this population has pigmented hulls and nipples. The average adult weight in extensive conditions is 41.3kg, with a low average daily gain (31g), but we must rescue the great ability to adapt and survive in extreme conditions where this animal develops. In all goat herds extensive management predominates, supplementing their diet with crop residues and mineralized salt occasionally. The whole herd is managed as one, there is no animal handling by categories, except for the extreme work they do in the kids during the first month of the lactation period. Key words: phenotypically, parameters, zoometrics, goats, interval, characterization